Inactivation of bacterial population in hide-soak liquors via direct electric current - BİRBİR, MERAL; BİRBİR, YAŞAR (ELSEVIER, 2008)
Inactivation of bacteria by electric currents has received much attention due to its high efficiency, low cost, and ease of application. Therefore, the antibacterial effect of passing 2 A direct electric current for 50 min on mesophilic bacteria in both first and main hide-soak liquors obtained from different tanneries in Tuzla-Istanbul, Turkiye was examined. The mesophilic bacterial numbers in the main hide-soak liquors were higher than that of the first hide-soak liquors. The total numbers of gram-negative bacteria (10(1)-10(4) CFU/mL) and halotolerant bacteria (10(3)-10(4) CFU/mL), in both first and main hide-soak liquors, were almost the same. The numbers of total of proteolytic and lipolytic mesophilic bacteria and the total of proteolytic and lipolytic halotolerant bacteria in the main hide-soak liquors were higher than that of the first hide-soak liquors. Mesophilic bacteria in the first (seven samples) and main (three samples) hide-soak liquors were inactivated after 20-30 min of electrical treatment. In the other four main hide-soak liquors, the inactivation occurred after 50 min of treatment. The most important result of this experiment is that there was a correlation between the voltage level and the numbers of bacteria in the electrolysis cell. The bacterial populations in the hide-soak liquors decreased proportionally to the voltage level until all of the bacterial population was inactivated. After the bacteria in the hide-soak liquors were completely destroyed by direct electric current, the voltage level started to increase. This important clue might be used to predict the inactivation time of all of the bacterial population in hide-soak liquors in the hide industry. It is suggested that the bacterial inactivation in hide-soak liquors by electrical treatment might be used in tanneries, which do not have a waste treatment system and discharge their effluents directly into environment. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: direct electric current; mesophilic bacteria; antibacterial activity; hide-soak liquors; hide industry; LISTERIA-MONOCYTOGENES; LEATHER; WATER; DISINFECTION; METABOLISM; BRINE; MILK